The influence factors of E-logistics implementation in China: The conceptual framework - Lisha, Guo; A. Jalil, Emy Ezura; Zainuddin, Nizamuddin (School of Technology Management and Logistics (STML), 2018)
Logistics plays the central role in delivering the products from manufacturers to consumers through the supply chain (Lee & Seo, 2017). That is the reason why the logistics industry has sharply increased when the global economy has digitized rapidly.After that, traditional logistics services transformed in electronic commerce logistics called e-logistics. Now, the e-logistic is put into practice all over the world.It involves circulation of goods throughout the industry. Thus it has a considerable effect on businesses (Lee & Seo, 2017) worldwide, particularly in developed nations such as United Kingdom (UK), Germany and Netherland. From 1999 to 2005, a dramatic growth was recorded in these countries. In United Kingdom (UK), the growth was approximately 720%, in Germany 1060% and in Netherland growth was recorded 1403% (Weltevreden, 2007a). Therefore, e-logistic activities are covering a wider scope.